Mortalidade por câncer de estômago e esôfago no Brasil entre os anos de 1995 a 2009 e projeções até 2029 - Giusti, Ângela Carolina Brandão de Souza (2015)
Studies which bring the estimates of incidence, mortality, trends and projections are very important for the health, since they are based on this data, new prevention and intervention policies are prepared. On this research, the objective was to analyze the mortality of stomach and esophagus cancer in the 5 Brazilian regions and in Brazil, from 1995 to 2009, and to make the projections up to 2029. All the data of the deaths caused by these types of cancer were obtained in the Sistema de Informação sobre Mortalidade (SIM), from the Brazilian Health Ministry. The data of the population from 1995 to 2009 were taken from the Instituto Brasileiro de Geografia e Estatística (IBGE) website. It was corrected through the proportional redistribution of the general deaths. The deaths included in the category of fatalities by signs, symptoms and undefined disorders were relocated, following the proportional distribution in which they happened in each of the chapters within the deaths by defined causes. The calculation of the standardized rates was done using the world population as a base through the Nordpred program, as well as the projections of the number of cases and the rates until the year 2029 using an age-period-cohort model. The results of the projections reveal that for the stomach and esophagus cancer an increase is expected in the total number of deaths in Brazil and all its regions. When comparing the evolution of the stomach cancer standardized mortality rates, an increase for the males in the north and northeast regions is observed and with the females in the northeast only. In the Midwest, South and Southeast regions, as well as the group analysis for Brazil, the projections indicate a reduction of the mortality rates in males and stability in females. In relation to the esophagus cancer, in the North and Northeast regions is expected an elevation of the standardized mortality rates until the last projected period for males and females. In the Midwest, Southeast and South regions the projections indicate a reduction of the rates, as well as in males in the group analysis for Brazil. In the data for Brazil, stability is observed in the female rates over the observed and projected periods. One can conclude mortality by gastro esophageal cancer is unevenly distributed in the Brazilian regions; however the projections indicate a reduction of those inequalities by the year 2029.